The Perceptions of Teachers and Students Towards the Ulul Albab Curriculum: A Case Study of SMAKL - Md Yusnan, Mohammad Baihaqi; Nik Abdullah, Nik Md. Saiful Azizi (IIUM Press, International Islamic University Malaysia, 2020)
Integrated curriculum has begun to take a positive lead in the educational development in Malaysia, where memorisation of the Qurʾān is integrated into the basic academic and Islamic subjects and is beginning to be implemented in many schools all over Malaysia. This integrated curriculum or commonly known as the Ulul Albab Curriculum has successfully been implemented over the years. This study therefore aims to find and assess the success factors through analysing the perceptions of those involved in the exercise. The study is quantitative in nature. Questionnaires were used as the instrumentation for data collection and were distributed to a total of 220 respondents: 50 teachers and 170 students from Sekolah Menengah Agama Kuala Lumpur (SMAKL). The findings of the study were derived from the obtained results of the questionnaire. The research theorises that students’ achievements in various aspects, from personality, individual skills and student discipline are key to measuring how far the curriculum has achieved its objectives. Considering this, the researchers propose that schools should further nurture all aspects of students’ growth; spiritual, physical, and mental so they can work the best in becoming influential models with various sets of skills. The Ulul Albab Curriculum as one of the few formal integrated curricula underthe Ministry of Education has to be given more emphasis and attention so that the curriculum can grow and become more outstanding. It isthe hope of many Muslim educational theorists that this curriculum will succeed in the future and can become an applicable mechanism to produce quality students who are not only masters of the academic field but also memorisers of the Qurʾan and knowledgeable scholars of religious subjects.